Moving toward the ugly: A politic beyond desirability - Mingus, Mia (Leaving Evidence, 2011)
*Femmes Of Color Symposium Keynote Speech, Oakland, CA (8/21/11)
Keywords: approches et analyses; capacitisme; corps; cours; discours dominant; fem3100; identités LGBTQIA2+; premier cycle; privilèges; queer; racisme; ressource en ligne; sexisme; sexualité; systèmes d'oppressions; thématiques